A study of multistage interconnection networks operating with wormhole routing and equipped with multi-lane storage. Issue 3 (4th May 2021) - Stergiou, Eleftherios
Abstract : Multistage interconnection networks (MINs) provide critical communication resources between network components with an attractive cost/performance relation. In this paper, a novel architecture for a MIN is proposed. In contrast to other existing networks, this new architecture operates via wormhole routing using a multi-lane equivalent-weighted fair queuing system. Associating the lane storage with each physical channel for movement of the flits allows for high levels of packet flow and makes the system more robust. The resulting flit scheduling schema has been studied thoroughly, and the results are presented in this manuscript. In addition to performance metrics, additional factors such as complexity, cost and reliability are investigated. Since a basic aim of the design of MINs is to achieve a good data flow control mechanism, this proposal is an extremely effective and robust solution. The rationale behind this innovative scheme is to introduce a more efficient network technology, thus providing a better quality of service (i.e. streaming media vs. file transfer). GRAPHICAL ABSTRACT: